2014
DOI: 10.1002/ep.12068
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and characterization of creation of geopolymers prepared from fly ash and metakaolin by X‐ray photoelectron spectroscopy method

Abstract: The formation of geopolymers from fly ash (FA) and metakaolin (MK) was investigated. The effect of different reactivity of FA and MK was studied by X‐ray photoelectron spectroscopy method. Geopolymer materials were obtained by an alkaline activation of aluminosilicate sources. The aim of this work is to develop methods for working properties prediction of geopolymer materials based on the starting materials. Selection of a geopolymerization scheme is found to be a key factor to realize a beneficial effect of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 16 publications
3
14
0
Order By: Relevance
“…A small change in specific surface area was observed for milled fly ashes MH and MS, increase of their specific surface area was by approximately only 20% and 26%, respectively. In our X-ray photoelectron microscopy spectra, we observed differences in formation of geopolymers from four different sources-MH,MS, F and G. Progressive monitoring these samples showed that the formation of the polymer chain is best in geopolymer prepared The peak positions of atoms of MH and MS polymers do not change too much, but the spectrum changes its shape, suggesting formation of intermediate silanol SiAOH group and production of basic siloxo Si-O-Si group in accordance with literature [1,14]. Solidification of the four samples indicates a significant decrease of oxygen.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…A small change in specific surface area was observed for milled fly ashes MH and MS, increase of their specific surface area was by approximately only 20% and 26%, respectively. In our X-ray photoelectron microscopy spectra, we observed differences in formation of geopolymers from four different sources-MH,MS, F and G. Progressive monitoring these samples showed that the formation of the polymer chain is best in geopolymer prepared The peak positions of atoms of MH and MS polymers do not change too much, but the spectrum changes its shape, suggesting formation of intermediate silanol SiAOH group and production of basic siloxo Si-O-Si group in accordance with literature [1,14]. Solidification of the four samples indicates a significant decrease of oxygen.…”
Section: Resultssupporting
confidence: 88%
“…The peak positions of atoms of MH and MS polymers do not change too much, but the spectrum changes its shape, suggesting formation of intermediate silanol SiOH group and production of basic siloxo Si‐O‐Si group in accordance with literature . Solidification of the four samples indicates a significant decrease of oxygen.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The negative charge of the aluminate groups is balanced by joining the alkali cations [15]. According to Davidovits [4], geopolymers has been described by the structural formula Mn[-(SiO 2 ) z -AlO 2 ) n .wH 2 O where M represents any alkali cations, z is 1, 2, 3, w is the number of water molecules, and n represents the degree of polycondensation.…”
Section: Geopolymer Chemical Structurementioning
confidence: 99%